Synthesis and Antifungal Investigation of Co(II), Ni(II) Complexes with Nitrogen, Oxygen and Sulphur Donor Ligands - Rai, B.K.; Shankar, Ravi; Pandey, S. (Asian Journal of Chemistry, 2010)
Mixed ligand complexes of the type [M(LH2)B2] where M = Co(II) and Ni(II), L = 1-hydroxy-10-mercapto-1,2:5,6:9,10-tribenzo-3,7-diaza- 1,3,5,7,9-decapentene (LH2), B = water, ammonia, phenyl isocyanide, quinoline, pyridine and α, β and γ-picolines. The ligand as well as metal complexes were characterized by physico-chemical technique. On the basis of above observations the geometry of the complexes were proposed to be octahedral. The LH2 behaves as binegative tetradentate ligand. The remaining coordination sites are satisfied by neutral molecules. The ligand as well as metal complexes were screened for their antifungal activity.